PENGEMBANGAN KEDELAI DI LAHAN HUTAN KAYU PUTIH KAB. GUNUNGKIDUL - Arif Anshori; Sukristiyonubowo (AGROISTA : Jurnal Agroteknologi, 2019)
Necessary of soybeans are increased with population growth and the food processing industry. However, land competition is heavier for development of soybean plants in Gunungkidul Regency. Soybean cultivation under the auspices of eucalyptus plants has a potential to overcome these problems. This study aim is to determine the potential for developing soybeans in the eucalyptus forest area of Gunungkidul Regency. This research is a combination of specific condition of soybean development in the eucalyptus forest area and review of research result. The result showed that soybeans under eucalyptus stands have the potential to be developed. Dena 1 and 2 superior soybean varieties are shade resistant varieties that can be cultivated under the stands of eucalyptus plants. Besides superior shade resistant varieties, technology components of soybean cultivation in eucalyptus forests include seeds, plant populations, control of plant pests, land preparation, fertilization, irrigation and harvesting. Keywords: soybean, eucalyptus